Effect of temperature and volume on the tensile and adhesive properties of photocurable resins. Issue 14 (26th May 2014) - Harding, David R.; Goodrich, Holly; Caveglia, Aaron; Anthamatten, Mitchell
ABSTRACT Knowing the mechanical properties of UV‐curable resins at cryogenic conditions is important to ongoing fusion‐energy research and to emerging aerospace applications. The tensile and interfacial shear strengths of two commercially available UV‐curable resins were measured at room‐temperature and cryogenic conditions for both bulk and reduced (subnanoliter) specimen volumes. The tensile properties of cured specimens are remarkably sensitive to both testing temperature and specimen size. For one type of resin, the cold (−150 °C) tensile strength of subnanoliter specimens is ∼9× larger (179 ± 19 MPa) than bulk values at room temperature. The interfacial shear strength between SiC fibers and small volumes of resin volumes is comparable to the bulk, room‐temperature tensile strength, but it varies over a wide range at −150 °C (15–53 MPa). All resins were fully cured, and an analysis of fractured surfaces revealed microstructural features. The enhanced strength in microscopic specimens may be related to inhomogeneous stress fields that develop during cure. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 936–945